Assessment of Soil Resource Potential of Warm Humid Kumaon Himalayas for Sustainable Productivity - R.P. Yadav and S.K. Singh, Ritu Nagdev, S.K. Mahapatra (Journal of the Indian Society of Soil Science, 2017)
Soil resource potential of a part of Almora district of Uttarakhand in humid Kumaon Himalayas covering different landforms and parent materials were assessed for sustainable productivity using remote sensing and GIS techniques. The study reveals that soil development depends mainly on physiographic position and parent material. Six soils viz., Maniagar, Panuanaula, Artola, Duram, Kaphalkhan and Dhaula Devi were identified occurring on ridge tops and side slopes with varying degree of slope gradients. Maniagar and Panuanaula soils originated from mica schist and occurred on steeply sloping side slopes and steeply sloping ridge tops, respectively. They were shallow to moderately shallow in depth, sandy loam to loamy sand in texture with coarse gravels and belonged to Entisols. They suffered from severe soil erosion and very low nutrient holding capacity [CEC ranging from 1.86 to 2.84 cmol(p+)kg-1] and rated as class-IV lands under land capability classification (LCC). These soils can be better used for agroforestry, agri-horticulture and pasture development. Artola soils occurred on moderately steeply sloping side slopes and were developed on quartzitic parent materials. They were moderately deep, loamy sand in texture with more than 35% coarse gravels in all the horizons and belonged to Entisols. They suffered from severe erosion and very low CEC [1.51 to 1.88 cmol(p+)kg-1] and were rated as class IV lands. They can be cultivated for agricultural crops with adoption of integrated nutrient management (INM) practices and appropriate soil and water conservation measures. Duram and Dhaula Devi soils occurred on moderately steeply sloping ridge tops whereas Kaphalkhan soils occured on moderately steeply sloping side slopes. These soils were developed on slate parent material. They were loam to clay loam in texture, well developed with cambic sub-surface diagnostic horizon and belonged to Inceptisols and rated as Class-III lands. They can be cultivated for agricultural crops with adoption of INM practices besides agroforestry, agri-horticulture and pasture development.